2012
DOI: 10.1186/1471-2148-12-207
|View full text |Cite
|
Sign up to set email alerts
|

Balancing selection and genetic drift at major histocompatibility complex class II genes in isolated populations of golden snub-nosed monkey (Rhinopithecus roxellana)

Abstract: BackgroundSmall, isolated populations often experience loss of genetic variation due to random genetic drift. Unlike neutral or nearly neutral markers (such as mitochondrial genes or microsatellites), major histocompatibility complex (MHC) genes in these populations may retain high levels of polymorphism due to balancing selection. The relative roles of balancing selection and genetic drift in either small isolated or bottlenecked populations remain controversial. In this study, we examined the mechanisms main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 93 publications
2
24
0
Order By: Relevance
“…These results agree with a large number of studies that show balancing selection on MHC PBR sites (e.g. Biedrzycka & Radwan, ; Luo et al., ). However, maximum‐likelihood methods detect historical periods of balancing selection during the evolutionary trajectory of a species (Garrigan & Hedrick, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results agree with a large number of studies that show balancing selection on MHC PBR sites (e.g. Biedrzycka & Radwan, ; Luo et al., ). However, maximum‐likelihood methods detect historical periods of balancing selection during the evolutionary trajectory of a species (Garrigan & Hedrick, ).…”
Section: Discussionsupporting
confidence: 92%
“…Similar empirical studies in mammalian endangered species have reported low MHC diversity in cheetahs ( Acinonyx jubatus , Castro‐Prieto et al., ), Tasmania devil ( Sarcophilus harrisii , Morris, Austin, & Belov, ), European bison ( Bison bonasus , Radwan, Kawałko, Wójcik, & Babik, ), giant panda ( Ailuropoda melanoleuca , Zhang, Wu, Hu, Wu, & Wei, ), mountain goat ( Oreamnos americanus , Shafer, Fan, Côté, & Coltman, ), and the golden snub‐nosed monkey ( Phinopithecus roxellana , Luo et al., ), but there are notable exceptions. For instance, balancing selection instead of genetic drift explained high MHC polymorphism in bottlenecked populations of the Finnish wolf ( Canis lupus , Niskanen et al., ) and in the Island fox ( Urocyon littoralis , Aguilar et al., ).…”
Section: Discussionmentioning
confidence: 56%
“…Genetic drift may, in fact, have a stronger effect on immune system or functional genes than on neutral genetic diversity (Bateson, Whittingham, Johnson, & Dunn, ; Froeschke & Sommer, ; Marsden et al., ) or may overwhelm the influence of selection in small populations (Luo, Pan, Liu, & Li, ; Miller & Lambert, ). In some cases, MHC diversity even declines faster than does neutral diversity (Bateson et al., ; Bollmer et al., ; Ejsmond & Radwan, ; Eimes et al., ; Sutton et al., , ); however, we saw a more rapid decline of neutral diversity compared to MHC diversity in the captive ring‐tailed lemur population at the DLC.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively lower genetic diversity, genetically distinct status and small population size of this population makes it more vulnerable to environmental change than the other two populations Luo, Pan, Liu, & Li, 2012;Pan et al, 2009). This arboreal species lives in temperate broadleaf and coniferous forests , and the impact of climate change on vegetation is expected to decrease the availability of its suitable habitat (Luo et al, 2015;Xiang et al, 2011).…”
Section: The Sichuan Snub-nosed Monkey (Rhinopithecus Roxellana)mentioning
confidence: 94%
“…This population is considered as a stand‐alone management unit (Chang, Luo, et al, ), determined to be a group of conspecific individuals among which the degree of connectivity is sufficiently low and thus should be monitored and managed separately (Palsbøll, Bérubé, & Allendorf, ; Taylor & Dizon, ). The relatively lower genetic diversity, genetically distinct status and small population size of this population makes it more vulnerable to environmental change than the other two populations (Li et al, ; Luo, Pan, Liu, & Li, ; Pan et al, ). This arboreal species lives in temperate broadleaf and coniferous forests (Chang, Liu, Yang, Li, & Vigilant, ), and the impact of climate change on vegetation is expected to decrease the availability of its suitable habitat (Luo et al, ; Xiang et al, ).…”
Section: Introductionmentioning
confidence: 99%